Improving Packaging Quality and Marketing Strategy for Bimo Special Honey - Salma Marhamni Husna; Mochammad Ilyas Junjunan (Institut Agama Islam Al-Fatimah Bojonegoro, 2025)
The community service program focused on improving the understanding and skills of micro, small, and medium enterprise (MSME) actors in Jelun Atas Village, Bimo, Probolinggo, designing product packaging and utilizing digital marketing strategies. The method employed was participatory rural appraisal (PRA), emphasizing active community involvement. The activities were divided into three phases: planning, implementation, and evaluation. During implementation, participants were provided with training on creating attractive and functional packaging and maximizing digital platforms for marketing. The results showed a significant improvement in participants’ knowledge and practices, as evidenced by a 50% increase in average scores from pretest to posttest. Participants expressed high satisfaction with the program, highlighting its practical and applicable benefits. This activity is expected to foster the growth of sustainable business practices and increase local competitiveness